2006
DOI: 10.1172/jci29218
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated epithelial NHE3 inhibition and barrier dysfunction are required for TNF-mediated diarrhea in vivo

Abstract: Acute T cell-mediated diarrhea is associated with increased mucosal expression of proinflammatory cytokines, including the TNF superfamily members TNF and LIGHT. While we have previously shown that epithelial barrier dysfunction induced by myosin light chain kinase (MLCK) is required for the development of diarrhea, MLCK inhibition does not completely restore water absorption. In contrast, although TNF-neutralizing antibodies completely restore water absorption after systemic T cell activation, barrier functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(198 citation statements)
references
References 62 publications
9
189
0
Order By: Relevance
“…While a primary barrier defect may be present in IBD kindreds 12-14 , it is also clear that epithelial barrier defects can be induced by inflammatory cytokines [15][16][17][18][19][20][21][22][23][24] . Recent work has demonstrated that barrier dysfunction induced by inflammatory processes can be due to epithelial damage as well as non-apoptotic regulation of tight junction permeability 19,22,[25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…While a primary barrier defect may be present in IBD kindreds 12-14 , it is also clear that epithelial barrier defects can be induced by inflammatory cytokines [15][16][17][18][19][20][21][22][23][24] . Recent work has demonstrated that barrier dysfunction induced by inflammatory processes can be due to epithelial damage as well as non-apoptotic regulation of tight junction permeability 19,22,[25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Many studies suggest that decreased gene expression/epithelial surface expression/activity of NHE3 and other sodium transporters relates to the incidence of absorptive diarrhea in IBD and animal colitis models. 39,51,52 However, other studies discount this to be the case. 51,53 CFTR remains critical to regulate electroneutral sodium chloride absorption and NHE3 regulation by augmenting its inhibition in a cAMP-dependent fashion.…”
Section: Cftr-inos Signaling Complexmentioning
confidence: 99%
“…Constitutive MLCK activation in the intestinal epithelium increases intestinal paracellular permeability and aggravates the severity of colitis in mouse models. However, blockage of MLCK activation can increase significantly the intestinal barrier function and ameliorate DSS-induced colitis [100] . PKC: PKC has a variety of isoforms that are involved in the pathogenesis of IBD by their effect on the mucus layer [101] , microbiota [34][35][36][37] , cell junction [64,65] and immune system.…”
Section: Of Ibdmentioning
confidence: 99%